Checklist of the Brachyura of the Brazilian Amazon Coastal Zone and knowledge status of their larval development - de Lima, Francielly Alcântara; Martinelli-Lemos, Jussara Moretto (Zootaxa, 2019)
This bibliographic review includes all brachyuran species listed for the Brazilian Amazon Coastal Zone (covering the occurrence of species in the states of Amapá, Pará, and Maranhão), with respective larval development either fully or partially described. Information provided include the current taxon name, taxon authorship, larval stages described, and habitat of the adult of each species. A total of 194 species were recorded in the study area. Of these, 49 (25%) have the larval stages completely described, 25 (13%) have incomplete descriptions of the larval development with at least one stage described, and most of them, 120 species (62%), do not have morphological descriptions of any larval stage. This is clearly a large gap that needs to be filled for the advancement of the knowledge of crab life histories in a unique area of coastal biodiversity. More so because this area faces threats from the pink shrimp fishery and oil prospection activities.